Design, development and evaluation of an instructional module on strategic arabic reading - Rouyan, Nurazan Mohmad (Kulliyyah of Education, International Islamic University Malaysia, 2015)
Studies have shown that most Malay learners of Arabic exhibit weak Arabic reading skills despite years of learning the language. Moreover, given that instructional practices in many Arabic language classes reflect a primary focus on grammar, strategic instruction is deemed to be quite challenging for most instructors. Hence, the purpose of this research was to design, develop and evaluate an instructional module on strategic Arabic reading as a proposed solution to enhancing skilled strategy use among undergraduate learners of Arabic when reading Arabic texts. The module developed comprised strategic reading lessons, together with recommended implementation conditions in the classroom. It was developed through four phases of the design and development research framework proposed by Reeves (2000): analysis, design and development, implementation, and reflection and refinement. The participants who were purposively sampled comprised eight experts: three Arabic language learning strategy research experts, three Arabic subject matter experts, an instructional design expert, and a reading expert; an instructor and two groups of learners (15 and 11 learners respectively). The participants evaluated the validity, practicality and effectiveness of the module through a four phase formative evaluation: the needs analysis, the pre-production evaluation, the production evaluation and the implementation evaluation. Qualitative research methods were employed for the evaluation which included interviews and consultations with experts, classroom observations, reflection group interviews with students and the instructor after each lesson, and think-aloud data collection sessions from students' pre and post reading task interviews and small-group works. Responses generated from participants in each phase were collated and analysed so that improvements could be made in the next phase. Findings indicated that, when implemented with all the critical characteristics of strategic reading instruction drawn from the needs analysis, the module has the potential to inculcate in learners a more strategic approach towards Arabic reading. Findings also suggested that users responded positively to the practicality and effectiveness of the module. Analysis of the reading task interviews and group works indicated that students generally developed a higher metacognitive awareness in reading and were able to use the strategies taught to construct meaning. The research concluded that careful observation of the design principles in the design of the module was the main contributing factor to the success of the module implementation. Finally, the study offers some implications and recommendations for the design of strategic instruction in the teaching and learning of Arabic and the strategic development of learners of Arabic.